Highly selective and efficient electroreduction of CO2 in water by quaterpyridine derivative‐based molecular catalyst noncovalently tethered to carbon nanotubes. Issue 1 (17th January 2022) - Reddu, Vikas; Sun, Libo; Li, Xiaogang; Jin, Huile; Wang, Shun; Wang, Xin
Abstract: A disubstituted quaterpyridine based cobalt complex non‐covalently tethered to multiwalled carbon nanotube (MWCNT) substrate, forming a hybrid catalyst, Co‐qpyCOOH/CNT, catalyzed the conversion of CO2 to CO under aqueous conditions. At an optimal and uniform loading, it exhibited remarkable catalytic activity, near‐exclusive selectivity, and high stability towards the formation of CO. At a mere cathodic potential of −0.65 V versus RHE ( η = 0.54 V), it achieved a high partial current density of −6.7 mA/cm 2 and a F.E.CO = 100%. In addition, with 20 h of stable operation, hydrogen evolution remained practically undetected. Its hybrid structure due to noncovalent immobilization on MWCNT imparted the intrinsic activity and much‐needed stability in performance whereas ‒COOH groups may stabilize the intermediates by acting as H‐bond donors, promoting catalytic activity. Tethering to a conductive solid substrate and tuning of the second sphere of coordination played an important role in its performance to achieve desired reduction product with high selectivity and activity. Abstract : Molecular electrocatalysts can efficiently convert carbon dioxide to fuels and feedstocks, helping to achieve the closing of carbon cycle. Heterogeneous quaterpyridine derivative immobilized on carbon nanotubes has been investigated for CO2 reduction reaction. In aqueous condition it could achieve the high activity, near‐unity selectivity, and high stability at a modest overpotential, outperforming many metal complexes reported so far.